Integrating protein visualisation in the classroom with StarBiochem. (16th June 2010) - Ceraj, I.; Riley, J.T.; Shubert, C.; Aleman, L.M.; Kosinski-Collins, M.; Rokop, M.E.; Vandiver, K.
Teaching about proteins, how their structure is specified and how in turn this influences their function has become an integral curriculum component for both introductory biology and biochemistry undergraduate courses. To understand how proteins work, students first learn about protein structure and its relationship to protein function. StarBiochem is a protein visualisation tool that is used to assist in teaching key structural biology concepts in an interactive manner. StarBiochem allows for the visualisation and manipulation of protein data bank (PBD) molecules in a 3D environment. In this manuscript, we provide examples of StarBiochem usage within high school and undergraduate curricula. Specifically, we will highlight how StarBiochem is currently used in undergraduate courses at the Massachusetts Institute of Technology (MIT), Brandeis University, and in high school outreach programs at the Broad Institute of Harvard and MIT and at the MIT Museum.